Rapid Calcification of Myocardium as Sequela from Severe Sepsis - S. Kunz, Andreas; Beissert, Matthias; Klink, Thorsten (Journal of Clinical Case Reports and Images, 2017)
A rare case of rapid myocardial calcification following severe sepsis is presented. The report outlines the temporal course, imaging findings, and plausible pathophysiologic mechanisms, including septic cardiomyopathy and calcium‑phosphate imbalance. Implications for critical care follow‑up and cardiology evaluation are discussed.
Keywords: Myocardial Calcification; Severe Sepsis; Septic Cardiomyopathy; Critical Care